Involvement of icaritin in the regulation of osteocyte exosomal microRNAs - Kaijia Zhang; Yujiang Liu; Yue Lu; Gongwen Liu; Xiaofeng Shen (Journal of Orthopaedic Surgery and Research)
Abstract Objective To explore the effects of Icaritin (ICA) on the regulation of osteocyte exosomal miRNAs and to promote the understanding of the potential molecular mechanisms involved in bone repair by ICA. Methods MLO-Y4 cells were treat with PBS or 10 µM ICA for 24 h and the supernatant was collected. Exosomes were isolated and purified according to standard methods, and identified by transmission electron microscopy, nanoparticle tracking analysis and protein blotting. Exosomal miRNAs were analysed by RNA sequencing. Results Osteocyte exosomes were successfully isolated and characterised. MiRNA sequencing showed that two known exosomal miRNAs (miR-128-3p, miR-30a-5p) were significantly up-regulated and two were significantly down-regulated (miR-5112, miR-1285) after ICA intervention. Conclusion Based on the findings, ICA regulates several miRNAs of osteocytes, which deepen our understanding of the therapeutic effects and mechanisms of ICA on skeletal diseases. The translational potential of this article Osteocytes are the most abundant cell type in bone tissue, of which the impact on bone homeostasis is still not clear. This study explored the impact of icaritin on osteocytes and their derived exosomes. By doing so, we hope to contribute to the understanding the therapeutic potential of ICA and osteocytes in maintaining bone health and treating conditions such as osteoporosis.